LINT‐Web: A Web‐Based Lipidomic Data Mining Tool Using Intra‐Omic Integrative Correlation Strategy (Small Methods 9/2021). Issue 9 (14th September 2021) - Li, Fengsheng; Song, Jia; Zhang, Yingkun; Wang, Shuaikang; Wang, Jinhui; Lin, Li; Yang, Chaoyong; Li, Peng; Huang, He
Abstract : Inside Front Cover In article number 2100206, Yang, Li, Huang, and co‐workers designed an interactive web‐based tool: LINT‐web that demonstrates a novel intra‐omics strategy to analyze multi‐omics data. This strategy combines lipidomics, proteomics, and genomics information tto data mining the new biological processes. For such reason, we design this cover illustration that shows each type of information is tunneling into the LINT‐web and generating the results.